Diseño de la Documentación para el Sistema de Gestión de Calidad en la empresa Musiforros GMP bajo los Lineamientos de la Norma Técnica Colombiana NTC ISO 9001:2015. (2021)
With this degree work, the documentation of the quality management system that applies to all types of companies is developed, but it can also be managed at the level of an SME (microenterprise), this is evidenced in the delivery of the results derived from the design of the documented information for the company MUSIFORROS GMP. The starting point of the project is given with a diagnosis which provides a result by means of a graph that illustrates how the company is currently in its organizational context as suggested by numeral 4.1 of the NTC ISO 9001; 2015 Standard, following The same guidelines also establish the needs and expectations of the interested parties, mission, vision and quality objectives, a PDCA cycle was developed through characterizations by process and an analysis of risks and opportunities was given, starting with a SWOT analysis and ending with a matrix that classified risks and opportunities of the company, other formats, manuals, records and procedures required by the standard as documented information are also taken into account and that are specific in the document and that as a result we comply with 80% of the documentation of the quality management systems, which is a notable improvement since at the time of making the diagnosis, the l We only had 10% of the documentation, this highlights the interest that MUSIFORROS GMP has in progressing every day by controlling and continuously improving the quality of the service and the commercialization of the products and the fulfillment of the proposed objectives.